Strengthening Governance of Education Costs: Towards Transparency, Accountability and Effectiveness - Muti Atus Sofiah; Shinta Hayu Asyisa Kurnia; Nur Anim Jauhariyah (ICO EDUSHA, 2024)
This research aims to analyze the implementation of the principles of transparency, accountability, efficiency and effectiveness in strengthening the governance of education costs at SMP Plus Darussalam and identify the obstacles faced. Using qualitative research methods, data was collected through interviews with the Deputy Head of Curriculum and related literature studies. The research results show that the implementation of accountability principles at SMP Plus Darussalam focuses on financial transparency, routine audits and a clear reporting system, thereby minimizing the risk of misuse of funds. Efficiency in allocating funds is implemented through a cashless payment system, which increases transaction transparency, reduces waste, and supports the development of facilities and improving the quality of learning. Obstacles in managing education costs still include a lack of transparency, limited resources, an administrative system that is not yet optimal, and low financial management capacity. To overcome this, strengthening the monitoring system, increasing capacity through training, and optimizing supporting technology are needed to ensure effective budget management. This research confirms that strengthening education cost governance through transparency, accountability, efficiency and effectiveness can increase stakeholder trust, optimize budget use, and support the achievement of sustainable and quality education goals.